Your new colleague is a robot. Is that ok? - Charles, Rebecca; Charalambous, George; Fletcher, Sarah R. (Taylor & Francis, 2015)
Human robot collaboration is a concept under development that will be applied within manufacturing environments in the near future to increase efficiency and quality. While there have been significant advances in technology to enable this progress there is still little known about the wider human factors issues of employing such systems in High Value Manufacturing environments. This paper sets out our current understanding of key organisational and individual factors which need to be explored.